Taxonomy of the genus Medhiama Bordoni, 2002 (Coleoptera: Staphylinidae, Staphylininae, Xantholinini) with descriptions of three new species - Zhou, Yu-Lingzi; Zhou, Hong-Zhang (Zootaxa, 2012)
The taxonomy of the genus Medhiama Bordoni, 2002 (Coleoptera: Staphylinidae, Staphylininae, Xantholinini) wasstudied in this paper, with the descriptions of three new species: Medhiama xiaolongmenensis sp. n. from Beijing andSichuan, M. liupanshanensis sp. n. from Ningxia and M. nigromagna sp. n. from Sichuan. The number of species of thegenus Medhiama therefore increased to 16. Five existing species are redescribed and/or their female diagnosticcharacteristics are also added. A key to 13 species is provided, not including the three which are known from singlefemales. The geographical distributions of the species are shown on maps. The type specimens of the new species are deposited in Institute of Zoology, Chinese Academy of Sciences (IZ-CAS).